Finite element analysis of gempita 8x8 underbelly deformation subjected to blast loading - Ahmad Raji, Kamarudin (2018)
Nowadays, armored personal carrier (APC) is largely used because of the revolution of war doctrine to carry the fighting element by vehicle, which means less infantry troops movement on foot. Malaysian Arm Forces has bought AV8 Gempita from Turkey and currently been deployed to carry out missions in our country. The APC will be faced lot of extreme conditions during war such as undulating terrain, landmine blast and armament fire. However, there are few studies done to assess AV8 Gempita performance when subjected to underbelly blast loading. The main objective of research is to simulate the AV8 Gempita hull deformation and acceleration when subjected to underbelly blast loading by using Finite Element Analysis. The simulation result has been used to determined AV8 Gempita capability to sustain blast loading STANAG 4569 level III as per claimed by manufacturer. The thesis then investigated the effects of changing different parameters, such as stand off distance, panel thickness, amount of explosive charge, and gap distance. Manual measurement on the hull body was conducted to obtain the measurement of hull AV8. The data is needed to make CAD modeling using Solidwork version 2016. The finite element simulation model was be analyzed using LS-DYNA 2013. Based on analysis, maximum deformation of AV8 hull is 88.6 mm when subjected to 10 kg of TNT that cause 59.6g to the occupants of vehicle. The hull body is proved can sustain that blast but it lose mobility and the occupants experienced severe injuries. The result from this research can be used to evaluate the capabilities of AV8 frame based on simulation and as initial reference for next research using experimental approach.